MORPHOLOGY OF THE MEDULLA OBLONGATA AT DEATH FROM BLOOD LOSS IN DIFFERENT PERIODS OF POSTMORTEM - Indaminov, S.I.; Zhumanov, Z.E. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
period with massive blood loss based on the study of the medulla oblongata. Material and research methods: We studied the structural changes in the medulla oblongata from 61 corpses of people who died from massive blood loss. In all the dead, the volume of internal blood loss ranged from 2500 to 4500 cm3, in addition, in all cases, external blood loss was observed. Results and discussion: With massive blood loss in the medulla oblongata, as the postmortal period increases, changes in both the nervous and vascular structures are observed. A gradual increase in destructive processes, reflecting the autolysis of neurons and blood vessels, is noted. In the dynamics of the increase in the postmortal period, there is an expansion of both perineuronal spaces (PNS) and perivascular spaces (PVS). The proportion of neurons and blood vessels respectively located in these spaces decreases. Conclusion: In the dynamics of the post-mortal period, a comparative characteristic of the expansion of perineural and perivascular spaces in the medulla oblongata allows us to judge the persistence of the manifestations of thanatogenesis of massive blood loss.